Rotary kilns : - Boateng, Akwasi Acheampong (Elsevier/Butterworth-Heinemann, 2008)
Rotary Kilns—rotating industrial drying ovens—are used for a wide variety of applications including processing raw minerals and feedstocks as well as heat-treating hazardous wastes. They are particularly critical in the manufacture of Portland cement. Their design and operation is critical to their efficient usage, which if done incorrectly can result in improperly treated materials and excessive, high fuel costs. This professional reference book will be the first comprehensive book in many years that treats all engineering aspects of rotary kilns, including a thorough grounding in the thermal and fluid principles involved in their operation, as well as how to properly design an engineering process that uses rotary kilns.